Creación musical a partir de la corporalidad - Barbot Antonoff, Alejandro Jarib (2023)
This work accounts for the processes of musical creation of a set of works composed in the context of the UFRGS/UdelaR Inter-institutional Master's program, between 2019 and 2021. It includes the aesthetic criteria and technical procedures conceived from corporality applied in the composition of those works. One of the most outstanding aspects is the use of the phenomenon of transmodality between sound and movement as a mechanism to generate music from dances pieces, to later generate dances pieces with which to generate new music. This line of musical composition from corporality has its origin in observations made in different instances of joint creation of music and dance pieces, which were systematized in this work through the elaboration of a theoretical framework proposal built mainly from concepts of music, psychology of music and philosophy of dance. The memorial describes the way in which the relationship between sound and corporality is used in the musical works, and delves into the procedures used in the composition of Ouroboros.